Analisis Pengaruh Environment Social, Governance Scores Terhadap Harga Saham Perusahaan Yang Terdaftar Pada Indeks Sri Kehati Tahun 2020-2022 - Alexander Yonathan Nugraha; Asumpta Evi Marlina; Anastasia Filiana Ismawati (FISCAL: Jurnal Akuntansi dan Perpajakan, 2024)
The purpose of this study is to analyze the influence of disclosure of environmental, social and governance (ESG) performance as reflected through ESG Scores on company share prices. The population in this study are companies listed on the SRI-KEHATI index for the 2020-2022 period. The research sample was selected based on purposive sampling criteria, so that 17 samples of companies listed on the SRI-KEHATI Index were selected between 2020-2022. The total observation data amounted to 51 data. Data collection uses secondary data sourced from annual and company sustainability reports. Analysis uses multiple linear regression. The research results show that the variables of environmental performance disclosure (environment scores), social performance disclosure (social scores), and governance performance disclosure (governance scores) have a significant negative effect on company share prices.